Examining the Effectiveness of the Fix-Up Strategy in Enhancing Junior High School Students’ Reading Comprehension - Aqilah Chanda; Mochtar Marhum; Andi Patmasari; Afrillia Anggreni (FOSTER: Journal of English Language Teaching, 2026)
This study investigated the effectiveness of the Fix-Up Strategy in improving reading comprehension among eighth-grade EFL learners. Reading comprehension remains a persistent challenge for many students due to limited vocabulary, difficulties in understanding sentence structures, and inadequate strategic awareness during reading. While previous studies have reported the effectiveness of the Fix-Up Strategy, limited attention has been given to its structured implementation among Indonesian junior high school EFL learners. Therefore, this study examined the effectiveness of a systematic five-step Fix-Up Strategy in enhancing students’ reading comprehension achievement. This study employed a quantitative approach using a quasi-experimental pretest–posttest control group design involving 54 eighth-grade students from a public junior high school in Indonesia, divided equally into experimental and control groups. Data were collected through reading comprehension tests and analyzed using descriptive and inferential statistics through SPSS. The findings revealed a substantial improvement in the experimental group, with the mean score increasing from 45.07 to 74.85, while the control group showed only a modest increase from 39.41 to 45.48. The Mann–Whitney U test further confirmed a statistically significant difference between groups (p = .000). These findings indicate that the structured Fix-Up Strategy effectively enhances students’ reading comprehension and offers practical pedagogical guidance for EFL teachers in promoting more active and metacognitive reading practices in junior high school classrooms.